The status of older persons in Africa: Challenges facing physiotherapists - S. L. Amosun (AOSIS, 1999)
In many African countries, there has been an increase in the number of older persons because of the gains in life expectancy made in the 20th century. The increase has led to concerns about how to provide necessary care for older persons as many on-going changes in the society threaten to erode the traditional support network. The paper identifies some of the many challenges facing physiotherapists in improving the status of older persons in Africa, and gives suggestions on overcoming the challenges.